Respostas
respondido por:
2
a₁ = -3
a₂ = 4
a₃ = 11
n = 15
r = 4 - (-3) = 7
a₁₅ = a₁ + (n - 1) * r
a₁₅ = -3 + (15 - 1) * 7
a₁₅ = -3 + 14 * 7
a₁₅ = -3 + 98
a₁₅ = 95
Soma dos termos da PA:
S₁₅ = [(a₁ + a₁₅) * n] ÷ 2
S₁₅ = [(-3 + 95) * 15] ÷ 2
S₁₅ = [92 * 15] ÷ 2
S₁₅ = 1380 ÷ 2
S₁₅ = 690
Espero ter ajudado. Valeu!
a₂ = 4
a₃ = 11
n = 15
r = 4 - (-3) = 7
a₁₅ = a₁ + (n - 1) * r
a₁₅ = -3 + (15 - 1) * 7
a₁₅ = -3 + 14 * 7
a₁₅ = -3 + 98
a₁₅ = 95
Soma dos termos da PA:
S₁₅ = [(a₁ + a₁₅) * n] ÷ 2
S₁₅ = [(-3 + 95) * 15] ÷ 2
S₁₅ = [92 * 15] ÷ 2
S₁₅ = 1380 ÷ 2
S₁₅ = 690
Espero ter ajudado. Valeu!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás